2005
DOI: 10.1051/0004-6361:20041466
|View full text |Cite
|
Sign up to set email alerts
|

H$\mathsf{_{\alpha}}$ observations of the star FK Com

Abstract: Abstract. High-resolution spectroscopic observations around the H α line of FK Com are presented. The analysis of the spectra reveals that: (a) the intensity of the R peak of the mean H α profile is larger than that of the V peak; (b) the intensities of the V and R emission peaks changes almost in anti-phase; (c) the ratio V/R varies in phase with V; (d) the total H α emission has a maximum at phase 0.75. The similarity of the H α profile of FK Com with those of the disk-like stars leads us to the conclusion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Kjurkchieva & Marchev (2005) found that the violet peak of the Hα spectra shows a quasi-sinusoidal change with a maximum at phase 0.75 and a minimum at 0.25. The red peak was at its maximum in Phase 0.25 and at minimum at 0.75, but the changes were not as significant as for the violet one.…”
Section: Correlating Chromospheric and Photospheric Activity Regionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Kjurkchieva & Marchev (2005) found that the violet peak of the Hα spectra shows a quasi-sinusoidal change with a maximum at phase 0.75 and a minimum at 0.25. The red peak was at its maximum in Phase 0.25 and at minimum at 0.75, but the changes were not as significant as for the violet one.…”
Section: Correlating Chromospheric and Photospheric Activity Regionsmentioning
confidence: 98%
“…Oliveira & Foing (1999) modelled highly variable Balmer line profiles and confirmed the complex circumstellar structures. Kjurkchieva & Marchev (2005) present highresolution Hα observations spanning over two years. The authors propose a model where FK Com is a binary system with a lowmass secondary star illuminating a circumstellar accretion disk.…”
Section: Introductionmentioning
confidence: 99%
“…The last column lists the extent of the records in years. Single stars are AB Dor, LQ Hya, V410 Tau, and FK Com (about its possible binarity see Kjurkchieva & Marchev 2005), and the rest (V833 Tau, EI Eri, V711 Tau, UZ Lib, UX Ari, HU Vir, IL Hya, XX Tri, HK Lac, and IM Peg) are synchronised, close binaries. In the case of binaries Table 1 gives the orbital period and the rotational period for single stars.…”
Section: The Samplementioning
confidence: 99%
“…Recently, Kjurkchieva & Marchev (2005) arrived at the conclusion from three-years of Hα spectroscopy, that the Hα behaviour of FK Com can only be explained if the star is indeed in a binary system with a high mass ratio. Figure 18 in Kjurkchieva & Marchev (2005) shows the binary scenario of FK Com using the same ephemeris as we have used in the present paper.…”
Section: The Possible Effect Of Binaritymentioning
confidence: 99%